Antidiabetic Therapy and Rate of Severe Hypoglycaemia in Patients with Type 2 Diabetes and Chronic Kidney Disease of Different Stages – A Follow-up Analysis of Health Insurance Data from Germany - Busch, Martin; Lehmann, Thomas; Wolf, Gunter; Günster, Christian; Müller, Ulrich Alfons; Müller, Nicolle (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background The presence of chronic kidney disease (CKD) influences the type of antiglycaemic therapy and the risk for hypoglycaemia.Methods In 2006, 2011 and 2016 health insurance data of people with diabetes type 2 were screened for CKD and the presence of severe hypoglycaemia (sHypo). The type of antihyperglycaemic therapy was recorded due to Anatomical Therapeutic Chemical (ATC) codes up to 3 months before suffering sHypo.Results The prevalence of CKD increased from 5.3% in 2006 to 7.3% in 2011 and 11.2% in 2016. Insulin-based therapies were used in 39.0, 39.1, and 37.9% of patients with, but only in 17.7, 17.4, and 18.8% of patients without CKD. Although the proportion of the CKD stages 1, 2 and 5 decreased, CKD stages 3 and 4 increased. The proportion of sHypo in CKD declined from 2006 (3.5%) to 2011 (3.0%) and 2016 (2.2%) but was still more than 10 times higher as compared to type 2 diabetic patients without CKD (0.3/0.2/0.2%) conferring a significantly higher probability of sHypo (OR 9.30, 95%CI 9.07–9.54) in CKD. The probability of sHypo was significantly lower in 2016 than in 2006 both in patients with (OR 0.58; CI 0.55–0.61) and without CKD (OR 0.70; CI 0.68–0.73).Conclusion The prevalence of CKD increased from 2006 to 2016. Patients with CKD exhibited a 9-fold increased probability of sHypo, especially in patients treated with insulin plus oral anti-diabetic drugs. However, the rate and risk for sHypo decreased over time, probably as a consequence of new antidiabetic treatment options, better awareness of sHypo, and changed therapy goals.
Keywords: complications; glycaemic control; hemoglobin A1C; insulin therapy; oral antidiabetic drugs